Facebook Usage for Educational Purposes / Soo Kum Yoke and Puteri Nur Hidayah Kamaludin - Soo, Kum Yoke; Kamaludin, Puteri Nur Hidayah (Universiti Teknologi MARA, Kedah, 2016)
Facebook offers an online platform which users can use for various purposes besides socializing. Majority of students use Facebook for entertainment rather than for education. Thus, Facebook is seen to have negative effects to learning. Some researchers have found that Facebook can affect academic achievements negatively. Yet others have shown that Facebook can provide opportunities to interact positively by promoting collaborative and cooperative learning to enhance learning outcomes. This study investigates the influence of Facebook on students’ attitude towards learning with the purpose of identifying the reasons that contribute to the impact of Facebook towards education among undergraduate students and the relationship between the use of Facebook and the academic performance. The research method applied is quantitative by using a survey for 30 undergraduates from different study programs. The data collected was analysed using descriptive analytical methods. The study found that there were a number of educational activities via Facebook that were done aside from using it for entertainment purposes and socializing.